L’Image au pied de la lettre. L’imagerie aménageuse au prisme de la (climate) fiction - Soline Nivet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The images produced by developers and real estate promoters are relatively homogeneous. Between commercial promise and optimistic prefiguration of future urban changes, they have little connection to other contemporary discourses, fictions and imaginaries of a more worried nature, especially in terms of climate change. Borrowing from literary theory, and in particular that which focuses on science-fiction and climate fiction, the article proposes other ways of reading these images, unveiling additional aspects that are ambivalent or unsettling.